The complexity of computing all subfields of an algebraic number field. (July 2019) - Szutkoski, Jonas; van Hoeij, Mark
Abstract: For a finite separable field extension K / k, all subfields can be obtained by intersecting so-called principal subfields of K / k . In this work we present a way to quickly compute these intersections. If the number of subfields is high, then this leads to faster run times and an improved complexity.